2022-RA-872-ESGO Percutaneous uterine needle biopsy with microscopic and array-CGH analyses in patients with suspicious myometrial tumors on MRI: a prospective study. (20th October 2022) - Smadja, Jeremy; Servois, Vincent; Pierron, Gaelle; Zein, Sophie El; Laas, Enora; Ramtohul, Toulsie; Tzanis, Dimitri; Watson, Sarah; Bonvalot, Sylvie
Abstract : Introduction/Background: Preoperative diagnosis of uterine tumors is of utmost importance to avoid inadvertent morcellation of leiomyosarcoma (LMS) and unnecessary hysterectomy in childbearing patients. There are no pathognomonic criteria for malignancy on Magnetic Resonance Imaging (MRI). The diagnosis of malignancy includes microscopic and genomic analyses with array-Comparative Genomic Hybridization (CGH). To date, no study has evaluated preoperative percutaneous uterine needle biopsy (PUB) with microscopic examination (M-PUB) and array-CGH analyses (MCGH-PUB). Methodology: This is a prospective single-center cohort study including all consecutive patients who had uterine LMS suspicion on MRI and for whom a PUB was performed. Microscopic and array-CGH analyses with genomic index (GI) count for myometrial tumors were performed in order to guide the therapeutic strategy. Smooth muscle tumors of uncertain malignancy potential (STUMPs) with a GI superior to 15 were assessed malignant, as well as tumors with a complex genomic profile (GI superior to 30 and/or malignant profile). Preoperative diagnoses based on M-PUB and MCGH-PUB were compared to the postsurgical pathological specimen or follow-up for non-operated tumors. Results: From November 2016 to February 2022, 34 patients were included. Based on surgical specimen (n=23) or follow up (n=11, including 4 metastasis), the final diagnoses were: 11 sarcomas and 23 non-sarcomas including 22 LM and one inflammatory myofibroblastic tumor[JS1] . The median follow-up was 12 months (IQR: 6–37). The diagnostic accuracy of M-PUB and MCGH-PUB were 94% and 100%. The sensitivity, specificity and Negative Predictive Value of MCGH-PUB were 100%, 100% and 100%. A high GI was significantly associated with malignancy (p<0·001). Genomic analyses allowed correct malignancy upgrade for four tumors after suspicious microscopic examination. There was no PUB complication and no dissemination on the biopsy track. Conclusion: MCGH-PUB is safe and accurate to discriminate pre operatively benign tumors from uterine sarcoma.